A process for removing fluorine, silicon and hardness from photovoltaic wastewater

Through the combination of chemical precipitation and flocculation precipitation, combined with air float filtration and ion adsorption, the problem of unsatisfactory removal of fluorine, silicon, and calcium plasma in photovoltaic wastewater is solved, and the removal of fluorine, silicon and silicon removal of wastewater is achieved It is hard, ensuring the stability and applicability of the effluent, laying the foundation for the secondary utilization of industrial tap water.

CN118894617BActive Publication Date: 2025-02-11SHANDONG HUANRUI ECOLOGICAL TECH CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411156865.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-08-22
Publication Date
2025-02-11
Estimated Expiration
2044-08-22

AI Technical Summary

Technical Problem

The removal rate of fluorine, silicon and calcium plasma in photovoltaic wastewater is not ideal, resulting in low fluorine and silicon removal rate in wastewater and increasing the hardness of wastewater, so it cannot be used directly as industrial tap water for secondary use.

Method used

Using a method of combining chemical precipitation and flocculation precipitation, the pH value of wastewater is adjusted by adding a composite precipitant and calcium hydroxide, combined with the use of a composite flocculant, flocculation precipitation is formed, and flocculation precipitation is formed through air float filtration, ion adsorption and Gore membrane. Filtration and other steps to remove fluorine, silicon, and calcium plasma from wastewater.

Benefits of technology

The removal of fluorine, silicon and hardness of photovoltaic wastewater has been achieved. The wastewater reaches the emission standards of Class I pollutants and the first-level standards. The effluent water quality is stable and suitable for industrial applications. It can be used as a secondary use of industrial tap water and realize the recycling of water resources.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005005231010000151
    Figure BDA0005005231010000151
  • Figure BDA0005005231010000161
    Figure BDA0005005231010000161
Patent Text Reader

Abstract

The present invention relates to the field of water treatment technology, and specifically to a process for removing fluorine, silicon and hardness from photovoltaic wastewater, including S1 chemical precipitation; S2 flocculation precipitation; S3 flotation filtration; S4 wastewater hardness removal; S5 ion adsorption pretreatment, and S6 ion adsorption. In the present invention, a combination of chemical precipitation and flocculation precipitation is adopted, and flotation filtration and ion resin exchange treatment are used to remove fluorine, silicon, calcium, magnesium and other ions from photovoltaic wastewater, and remove fluorine, silicon and hardness from wastewater, so that photovoltaic wastewater meets the first-class pollutant emission standard and the first-class standard, and the effluent water quality is stable, suitable for industrial application, and can be used as industrial tap water for secondary use to achieve the recycling of water resources.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of water treatment, and in particular to a process for removing fluorine, silicon and hardness from photovoltaic wastewater. Background Art

[0002] Under the severe situation of global fossil energy being exhausted, photovoltaic power generation technology has been continuously improving, and industrialization technology has basically matured. Countries around the world have successively issued a series of regulations and policies to promote the development of the photovoltaic industry. In the future, the photovoltaic industry will enter a period of rapid development for a considerable period of time. The photovoltaic industry is also a high-water-consuming and high-pollution industry. In most areas of my country where water resources are scarce and the water environment is deteriorating, it is a restricted development industry. The deep treatment and reuse technology of photovoltaic wastewater has solved the bottleneck problem that restricts the development of the photovoltaic industry from the perspective of improving the carrying capacity of water resources. Photovoltaic wastewater mainly comes from the cutting, grinding, fine grinding, polishing and other processes of its production process. Its water quality has the characteristics of high fluorine, high salt, high silicon, high nitrogen and low pH. In the process of processing to meet the battery industry emission standards, the company uses a large amount of calcium chloride and calcium hydroxide, resulting in a particularly high concentration of chloride ions and calcium ions in the wastewater. Although the company's drainage has reached the industry emission standards and the concentration of conventional pollutants in the sewage is not high, the silicon, calcium and fluorine in the ionic indicators have become the key factors restricting deep treatment and reuse, and generally encounter the dilemma that downstream sewage treatment facilities are unwilling to accept it.

[0003] For example, Chinese patent CN112158983A discloses a high-efficiency silicon removal and fluorine removal system and method for photovoltaic wastewater, which includes a homogenization regulating tank, a shallow flotation unit, a primary fluorine removal and silicon removal unit and a secondary fluorine removal unit connected in sequence. The sludge generated by the system is transported out after deep dehydration. A self-priming pump is provided between the homogenizing regulating tank and the shallow flotation unit. The shallow flotation unit, the primary silicon removal and fluorine removal unit and the secondary fluorine removal unit are connected by a gravity flow pipeline. The sludge generated by the system is pumped to the deep dehydration system through the sludge pump, and the sewage enters the subsequent treatment unit after silicon removal and fluorine removal. The technical scheme saves the dosage and reduces the operation cost while ensuring the silicon removal and fluorine removal effect by reasonably arranging the treatment procedures, thereby ensuring the stable operation of the subsequent treatment system. However, in the process of silicon removal and fluorine removal, fluorine and silicon combine with calcium ions to form calcium silicate and calcium fluoride. In the process of flocculation and sedimentation, due to the limited strength of the physical bonding between them, some small particles of calcium silicate and calcium fluoride will separate from the floccules and continue to be free in the wastewater, resulting in unsatisfactory fluorine and silicon removal rates in the wastewater. In addition, the excessive calcium ions introduced into the wastewater increase the hardness of the wastewater, resulting in that the treated wastewater can meet the discharge requirements but cannot be directly used as industrial tap water for secondary use. Summary of the invention

[0004] In view of the problems existing in the prior art, the purpose of the present invention is to provide a process method for removing fluorine, silicon and hardness from photovoltaic wastewater, which can remove fluorine, silicon, calcium, magnesium and other ions in photovoltaic wastewater, achieve fluorine removal, silicon removal and hardness removal of wastewater, so that photovoltaic wastewater meets the first-class pollutant emission standards and primary standards, and the effluent water quality is stable, suitable for industrial application, and can be reused as industrial tap water to achieve the recycling of water resources.

[0005] To achieve the above object, the present invention provides the following technical solutions:

[0006] A process for removing fluorine, silicon and hardness from photovoltaic wastewater, specifically comprising the following steps:

[0007] S1 Chemical Precipitation

[0008] Add composite precipitant and calcium hydroxide to photovoltaic wastewater and stir thoroughly until the pH value of the wastewater is 9-10;

[0009] S2 flocculation precipitation

[0010] Add a composite flocculant to the wastewater obtained in S1, stir thoroughly until flocculation precipitation is formed, and collect the supernatant;

[0011] S3 air flotation filtration

[0012] The supernatant obtained from S2 is pressurized and dissolved with air and then enters the flotation chamber, where the colloids and suspended matter formed in the water are separated, the scum is removed from the surface of the water body, and the treated wastewater is collected;

[0013] S4 Wastewater Hardness Removal

[0014] According to the Ca content in wastewater 2+ and Mg 2+ Weigh sodium hydroxide and sodium carbonate in an amount 2-3 times the total mass of the content, and then prepare them into reagents with a concentration of 10-18wt% respectively, and add them to the system reactor at the same time. The residence time of the wastewater in the hardness removal reactor is 60-80min;

[0015] S5 ion adsorption pretreatment

[0016] After the wastewater passes through the dosing and hardness removal reactor, it enters the Gore membrane filter. The pH of the effluent from the Gore membrane filter is adjusted, using hydrochloric acid as the reagent, and the pH value is adjusted to 6.0-6.5;

[0017] S6 ion adsorption

[0018] The wastewater obtained in S5 is adsorbed and removed by ion exchange resin, and after the ion exchange resin is saturated with adsorption, 3-7wt% citric acid is used for elution.

[0019] As a further preferred embodiment of the present invention, the composite precipitant is added in an amount of 8-15% of the total amount of wastewater;

[0020] The calcium hydroxide is added in an amount of 10-18% of the total amount of wastewater;

[0021] The composite flocculant is added in an amount of 3-5 g / L;

[0022] The pressure of the pressurized dissolved gas is 4-6N.

[0023] As a further preferred embodiment of the present invention, the Gore membrane filter has the following main operating processes: filtration, exhaust, pressure relief, backwashing, sedimentation, and slag discharge. The main operating parameters are: filtration pressure 0.01-0.10 MPa, filtration time 1500-3500 s, exhaust time 10-18 s, backwashing time 10-20 s, sedimentation time 20-50 s, and slag discharge time 10-15 s.

[0024] The flow rate of the resin adsorption column of the ion exchange resin is controlled at 10-13 BV.

[0025] As a further preferred embodiment of the present invention, the composite precipitant is prepared by the following method:

[0026] 1) deionized water, sodium citrate solution, anhydrous ethanol, ammonia water and polyvinyl pyrrolidone hexanol solution are mixed uniformly to obtain a microemulsion, and then the microemulsion is mixed uniformly with tetraethoxysilane in a volume ratio of (4-5):1, and the mixture is reacted at a constant temperature of 40-45°C for 4-9h. After the reaction is completed, the product is repeatedly washed with anhydrous ethanol and deionized water and then dried to obtain silica nanowires;

[0027] 2) Stirring and dissolving polyethylene glycol into deionized water, then adding sodium molybdate and thiourea in sequence, stirring and dissolving fully, then adding polyvinyl pyrrolidone and silica nanowires, stirring and dispersing uniformly, placing in a high-pressure reactor, stirring at 150-200 r / min, and reacting at a constant temperature of 220-230° C. for 8-15 hours, cooling to room temperature after the reaction is completed, repeatedly washing with anhydrous ethanol and deionized water, and drying to obtain a composite nanomaterial, dispersing the porous material in deionized water, and then adding the composite nanomaterial, mechanically stirring at 1000-1500 r / min for 1-3 hours, and then ultrasonically treating at 300-500W for 30-50 minutes to obtain a composite porous material;

[0028] 3) In a constant temperature water bath at 50-60°C, add β-cyclodextrin to a mixture of ethanol and deionized water in a volume ratio of 1:(2.0-2.5), stir thoroughly to dissolve, then slowly add lime, calcium chloride and the composite porous material, stir magnetically for 3-5 hours, then cool naturally to room temperature, and refrigerate at 3-5°C overnight, pour off the supernatant, wash repeatedly with ethanol and deionized water, and freeze-dry for 3-5 hours to obtain a composite precipitant.

[0029] As a further preferred embodiment of the present invention, the volume ratio of the deionized water, sodium citrate solution, anhydrous ethanol, and ammonia polyvinyl pyrrolidone hexanol solution is (3-5):1:(10-15):1:(100-180);

[0030] The sodium citrate solution has a concentration of 12-16 wt %;

[0031] The aqueous ammonia has a concentration of 25-27 wt %;

[0032] The polyvinyl pyrrolidone hexanol solution has a concentration of 50-56 wt %.

[0033] As a further preferred embodiment of the present invention, the ratio of the polyethylene glycol stirring, deionized water, sodium molybdate, thiourea, polyvinyl pyrrolidone, and silica nanowires is (30-50) mL: (50-100) mL: (1.0-1.5) g: (1.8-2.7) g: (0.15-0.18) g: (5-10) g;

[0034] The ratio of the porous material, deionized water, and composite nanomaterial is (5-10) g: (800-1200) mL: (3-6) g;

[0035] The ratio of the β-cyclodextrin, the mixed solution, lime, calcium chloride and the composite porous material is (10-15) g: (60-100) mL: (0.3-0.7) g: (0.2-0.5) g: (20-25) g.

[0036] As a further preferred embodiment of the present invention, the composite flocculant is composed of an aluminum salt coagulant, a polyacrylamide flocculant and a flocculant enhancer in a mass ratio of 1:(1-2):(0.1-0.3);

[0037] The flocculant enhancer is prepared by the following method:

[0038] 1) Potassium antimony tartrate is dissolved in deionized water, and after magnetic stirring for 10-20 minutes, polyvinyl pyrrolidone is added, and stirring is continued for 10-20 minutes, and then thioacetamide is added to the resulting mixed solution, and the mixture is fully stirred to obtain a reaction solution;

[0039] 2) The porous material is ultrasonically cleaned with acetone, distilled water and ethanol for 10-20 minutes respectively, and then added to the reaction solution after drying. After ultrasonic treatment for 10-20 minutes, it is transferred to a reactor, sealed and placed in an oven, and heated at a constant temperature of 180-185° C. for 25-30 hours. After the reaction is completed, it is cooled to room temperature, the product is centrifuged, repeatedly washed with deionized water, and dried.

[0040] As a further preferred embodiment of the present invention, the ratio of potassium antimony tartrate, deionized water, polyvinyl pyrrolidone and thioacetamide is (0.8-1.5) mol: (80-150) mL: (0.4-0.7) g: (1.5-2.6) mol;

[0041] The ratio of the porous material to the reaction solution is (3-7) g: (100-150) mL;

[0042] The ultrasonic treatment has a power of 200-300W.

[0043] As a further preferred embodiment of the present invention, it is characterized in that the porous material is prepared by the following method:

[0044] 1) dispersing polyvinyl pyrrolidone in acetonitrile, adding p-phenylenediamine and trimesic acid aldehyde, ultrasonically treating for 10-15 minutes, then adding scandium trifluoromethanesulfonate, stirring for 5-10 minutes, standing at room temperature for 6-10 hours and then centrifuging;

[0045] 2) The obtained product is washed repeatedly with anhydrous ethanol and 1,4-dioxane respectively, and then dispersed in a mixed solution consisting of 1,4-dioxane, mesitylene, deionized water and glacial acetic acid, and crystallized at 50-55° C. for 12-15 hours; after the reaction is completed, it is cooled to room temperature, centrifuged to separate the mother liquor, repeatedly washed with anhydrous ethanol, dispersed in n-octane and stirred for 12-15 hours to remove impurities, and dried after centrifugal separation to obtain a porous material.

[0046] As a further preferred embodiment of the present invention, the composite flocculant is prepared by the following method:

[0047] The ratio of polyvinyl pyrrolidone, acetonitrile, p-phenylenediamine, benzene trimethylenedialdehyde, scandium trifluoromethanesulfonate, 1,4-dioxane, mesitylene, deionized water, and glacial acetic acid is (200-300) mg: (15-25) mL: (0.23-0.28) mmol: (0.15-0.20) mmol: (1-3) mg: (10-13) mL: (2.5-3.6) mL: (2.5-3.6) mL: (3.5-5.0) mL;

[0048] The ultrasonic treatment has a power of 200-300W;

[0049] The stirring speed is 500-800r / min.

[0050] Compared with the prior art, the present invention has the following beneficial effects:

[0051] In the present invention, a combination of chemical precipitation and flocculation precipitation is adopted. First, chemical precipitation is used to treat the wastewater in a primary manner. A composite precipitant and calcium hydroxide are added to the wastewater to adjust the pH value of the wastewater to 9-10, and sufficient calcium ions are provided. In a strong alkaline environment, calcium ions are combined with fluoride ions and silicate to generate calcium fluoride precipitates and calcium silicate precipitates to remove fluoride ions and silicon ions in the wastewater. At the same time, with the use of a composite flocculant, some free small particles of calcium fluoride and calcium silicate in the wastewater can be adsorbed and agglomerated to make them settle. At the same time, Sodium hydroxide and sodium carbonate are used as hardness removal agents to remove the calcium ions and magnesium ions originally contained in the wastewater, as well as the excess calcium ions introduced during the chemical sedimentation process. The Gore membrane filter can also be used to remove suspended particles in the wastewater, reduce the hardness of the effluent, and remove a large amount of residue in the wastewater system. Finally, the ion exchange resin adsorption unit can be used to adsorb and remove calcium and magnesium ions in the wastewater. The hardness of the resin effluent can reach less than 1 mg / L. The effluent can be used as a good water source for subsequent unit treatment or use, thereby achieving efficient removal of fluorine, silicon, calcium, magnesium and other ions in the wastewater.

[0052] The composite precipitant introduced in the present invention utilizes the Schiff base reaction between two monomers, p-phenylenediamine and trimesic acid aldehyde, to synthesize a porous material with a multi-chamber structure through a crystallization method, and then the silicon dioxide nanowires synthesized by a one-pot reverse microemulsion method are used as deposition carriers, and added together with polyethylene glycol and polyvinyl pyrrolidone into a reaction system of molybdenum disulfide, and a large amount of nano-flower-shaped molybdenum sulfide is deposited on the surface of the silicon dioxide nanowires through a hydrothermal reaction, thereby obtaining a composite nanomaterial, and the composite nanomaterial is embedded in the pores of the porous material through mechanical stirring and ultrasonic action, and the composite nanomaterials and the composite nanomaterials and the porous material are bonded to each other. The surface nanoflowers are used as connecting nodes between the framework structures to form a stable cross-linking network, and the original chambers of the porous material are further subdivided, thereby forming a composite porous material with a high cross-linking density; then β-cyclodextrin is used as the wall material, lime and calcium chloride are used as the core material, and are added to the wall material liquid together with the composite porous material. In the process of microencapsulation embedding of the core material, due to the capillary effect of the porous structure of the composite porous material, during the sufficient stirring process, the core material and the wall material are easily infiltrated into the pores of the composite porous material, and the embedding process is completed in the internal chamber, and through refrigeration and freeze-drying, the internal cavity of the composite porous material is microencapsulated. A large number of calcium ion microcapsules are formed in the chamber, thereby obtaining a composite precipitant; by adding the composite precipitant to the wastewater, during the sufficient stirring process, the suspended particles in the wastewater will collide with the composite precipitant, thereby causing the wall material of the calcium ion microcapsules in the composite precipitant to rupture, and the embedded calcium ions will be slowly released for treatment, but due to the capillary effect of the porous structure of the composite precipitant, it will have a certain adsorption force on the calcium ions, resulting in a relatively slow overflow of the calcium ions. At the same time, the fluoride ions and silicate ions in the wastewater will also move to the pores of the composite precipitant under the capillary effect, thereby accelerating the fluoride ions, silicate ions and calcium The combination of ions, the two meet and react in the pores of the composite precipitant to form calcium fluoride and calcium silicate, and embed them in the pores. The highly cross-linked network structure will also limit the solidification of calcium fluoride and calcium silicate, making it difficult for calcium fluoride and calcium silicate to separate from the composite precipitant. As the amount of calcium fluoride and calcium silicate generated increases, the pore structure of the composite precipitant is continuously filled, causing the weight of the composite precipitant to increase continuously, and thus it settles to the bottom of the wastewater, thereby achieving efficient removal of fluoride ions and silicon ions in the wastewater. In addition, the adsorbed and fixed calcium fluoride and calcium silicate are not easy to desorb, so that there is basically no free small particles of calcium fluoride and calcium silicate in the wastewater.

[0053] At the same time, the composite flocculant in the present invention is composed of an aluminum salt coagulant, a polyacrylamide flocculant and a flocculant enhancer, wherein the aluminum salt coagulant and the polyacrylamide flocculant can strongly adsorb colloidal particles such as fluorine and silicon in the wastewater, so that the colloids are condensed to form tiny floccules. At the same time, the flocculant enhancer also uses a porous material as a carrier, potassium antimony tartrate and thioacetamide as an antimony source and a sulfur source, respectively, to form a reaction solution, the porous material is washed and added to the reaction solution, and a hydrothermal reaction is carried out after being fully dispersed, and the generated antimony sulfide nanoparticles are deposited and attached to the surface of the porous material, and as the hydrothermal reaction proceeds, the antimony sulfide nanoparticles agglomerate with each other, as shown in the surface Some network structures grow on the surface, and with the extension of reaction time, the deposited antimony sulfide nanoparticles gradually decrease, and the surface of the porous material is covered with the antimony sulfide network structure with a honeycomb structure, so as to obtain a flocculation enhancer with a multi-network structure covering layer on the surface and a porous structure inside; when the flocculation enhancer is added to the wastewater, the surface covering layer acts as a filter, which can block the large particles in the wastewater from being adsorbed into the interior of the flocculation enhancer, avoiding the clogging of the internal porous structure, so that it can continue to adsorb tiny flocculants such as fluorine and silicon in the wastewater to the surface to form agglomerations through capillary action, thereby causing sedimentation, thereby further realizing the removal of fluorine and silicon in the wastewater.

[0054] In the present invention, a combination of chemical precipitation and flocculation precipitation is adopted, and flotation filtration and ion resin exchange treatment are used to remove fluorine, silicon, calcium, magnesium and other ions in photovoltaic wastewater, thereby achieving fluorine removal, silicon removal and hardness removal of wastewater, so that photovoltaic wastewater meets the first-class pollutant emission standards and primary standards, and the effluent water quality is stable, suitable for industrial application, and can be reused as industrial tap water to achieve the recycling of water resources. DETAILED DESCRIPTION

[0055] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0056] In the embodiment of the present invention, the compound precipitant is added in an amount of 8% of the total amount of wastewater; the calcium hydroxide is added in an amount of 10% of the total amount of wastewater; the compound flocculant is added in an amount of 3g / L; the pressure of pressurized dissolved air is 4N;

[0057] The main operation process of Gore membrane filter is filtration, exhaust, pressure relief, backwashing, sedimentation and slag discharge. The main operation parameters are: filtration pressure 0.10MPa, filtration time 3500s, exhaust time 18s, backwashing time 20s, sedimentation time 50s, slag discharge time 15s;

[0058] The flow rate of the resin adsorption column of the ion exchange resin was controlled at 13 BV.

[0059] In the embodiment of the present invention, the preparation method of the porous material is as follows:

[0060] 1) Disperse 200 mg of polyvinyl pyrrolidone in 15 mL of acetonitrile, add 0.23 mmol of p-phenylenediamine and 0.15 mmol of trimesaldehyde, treat with 200 W ultrasound for 10 min, then add 1 mg of scandium trifluoromethanesulfonate, stir at 500 r / min for 5 min, stand at room temperature for 6 h, and then centrifuge;

[0061] 2) The obtained product was repeatedly washed with anhydrous ethanol and 1,4-dioxane, respectively, and then dispersed into a mixed solution consisting of 10 mL 1,4-dioxane, 2.5 mL mesitylene, 2.5 mL deionized water and 3.5 mL glacial acetic acid, and crystallized at 50° C. for 12 h; after the reaction was completed, it was cooled to room temperature, centrifuged to separate the mother liquor, repeatedly washed with anhydrous ethanol, dispersed in n-octane and stirred for 12 h to remove impurities, and dried after centrifugal separation to obtain a porous material.

[0062] Example 1

[0063] A process for removing fluorine, silicon and hardness from photovoltaic wastewater, characterized in that it specifically comprises the following steps:

[0064] S1 Chemical Precipitation

[0065] Add composite precipitant and calcium hydroxide to photovoltaic wastewater and stir thoroughly until the pH value of the wastewater is 9-10;

[0066] S2 flocculation precipitation

[0067] Add a composite flocculant to the wastewater obtained in S1, stir thoroughly until flocculation precipitation is formed, and collect the supernatant;

[0068] S3 air flotation filtration

[0069] The supernatant obtained from S2 is pressurized and dissolved with air and then enters the flotation chamber, where the colloids and suspended matter formed in the water are separated, the scum is removed from the surface of the water body, and the treated wastewater is collected;

[0070] S4 Wastewater Hardness Removal

[0071] According to the Ca content in wastewater 2+ and Mg 2+ Weigh sodium hydroxide and sodium carbonate in an amount twice the total mass of the content, and then prepare them into 10wt% reagents respectively, and add them into the system reactor at the same time. The residence time of the wastewater in the hardness removal reactor is 60min;

[0072] S5 ion adsorption pretreatment

[0073] After the wastewater passes through the dosing and hardness removal reactor, it enters the Gore membrane filter. The pH of the effluent from the Gore membrane filter is adjusted, using hydrochloric acid as the reagent, and the pH value is adjusted to 6.0;

[0074] S6 ion adsorption

[0075] The wastewater obtained in S5 is adsorbed and removed by ion exchange resin, and after the ion exchange resin is saturated with adsorption, 3wt% citric acid is used for elution.

[0076] Wherein, the preparation method of the composite precipitant is as follows:

[0077] 1) Deionized water, a 12 wt% sodium citrate solution, anhydrous ethanol, a 25 wt% ammonia solution and a 50 wt% polyvinylpyrrolidone hexanol solution were mixed uniformly in a volume ratio of 3:1:10:1:100 to obtain a microemulsion, and then the microemulsion was mixed uniformly with tetraethoxysilane in a volume ratio of 4:1, and the mixture was reacted at a constant temperature of 40°C for 4 hours. After the reaction was completed, the product was repeatedly washed with anhydrous ethanol and deionized water and then dried to obtain silica nanowires;

[0078] 2) 30 mL of polyethylene glycol was stirred and dissolved in 50 mL of deionized water, and then 1 g of sodium molybdate and 1.8 g of thiourea were added in sequence. After sufficient stirring and dissolution, 0.15 g of polyvinyl pyrrolidone and 5 g of silica nanowires were added. After sufficient stirring and dispersion, the mixture was placed in a high-pressure reactor and stirred at 150 r / min for 8 h at 220 ° C. After the reaction was completed, the mixture was cooled to room temperature, washed repeatedly with anhydrous ethanol and deionized water, and then dried to obtain a composite nanomaterial. 5 g of the porous material was dispersed in 800 mL of deionized water, and then 3 g of the composite nanomaterial was added. The mixture was mechanically stirred at 1000 r / min for 1 h, and then subjected to 300 W ultrasonic treatment for 30 min to obtain a composite porous material.

[0079] 3) In a constant temperature water bath at 50°C, add 10 g of β-cyclodextrin to 60 mL of a mixture of ethanol and deionized water in a volume ratio of 1:2, stir thoroughly to dissolve, then slowly add 0.3 g of lime, 0.2 g of calcium chloride and 20 g of the composite porous material, stir magnetically for 3 h, then cool naturally to room temperature, and refrigerate at 3°C ​​overnight, pour off the supernatant, wash repeatedly with ethanol and deionized water, and freeze-dry for 3 h to obtain a composite precipitant.

[0080] Among them, the composite flocculant is composed of aluminum salt coagulant, polyacrylamide flocculant and flocculant enhancer in a mass ratio of 1:1:0.1;

[0081] The preparation method of the flocculation enhancer is as follows:

[0082] 1) 0.8 mol potassium antimony tartrate was dissolved in 80 mL deionized water, and after magnetic stirring for 10 min, 0.4 g polyvinyl pyrrolidone was added, and stirring was continued for 10 min. Then, 1.5 mol thioacetamide was added to the resulting mixed solution, and the mixture was fully stirred to obtain a reaction solution;

[0083] 2) 3 g of the porous material was ultrasonically cleaned with acetone, distilled water and ethanol for 10 min respectively, dried and added to 100 mL of reaction solution. After ultrasonic treatment for 10 min, it was transferred to a reactor, sealed and placed in an oven, heated at 180°C for 25 h, cooled to room temperature after the reaction was completed, the product was centrifuged, repeatedly washed with deionized water, and dried.

[0084] Example 2

[0085] A process for removing fluorine, silicon and hardness from photovoltaic wastewater, characterized in that it specifically comprises the following steps:

[0086] S1 Chemical Precipitation

[0087] Add composite precipitant and calcium hydroxide to photovoltaic wastewater and stir thoroughly until the pH value of the wastewater is 9.5;

[0088] S2 flocculation precipitation

[0089] Add a composite flocculant to the wastewater obtained in S1, stir thoroughly until flocculation precipitation is formed, and collect the supernatant;

[0090] S3 air flotation filtration

[0091] The supernatant obtained from S2 is pressurized and dissolved with air and then enters the flotation chamber, where the colloids and suspended matter formed in the water are separated, the scum is removed from the surface of the water body, and the treated wastewater is collected;

[0092] S4 Wastewater Hardness Removal

[0093] According to the Ca content in wastewater 2+ and Mg 2+ 2.5 times the total mass of the content, weigh sodium hydroxide and sodium carbonate respectively, and then prepare them into reagents with a concentration of 15wt%, and add them to the system reactor at the same time. The residence time of the wastewater in the hardness removal reactor is 70min;

[0094] S5 ion adsorption pretreatment

[0095] After the wastewater passes through the dosing and hardness removal reactor, it enters the Gore membrane filter. The pH of the effluent from the Gore membrane filter is adjusted, using hydrochloric acid as the reagent, and the pH value is adjusted to 6.5;

[0096] S6 ion adsorption

[0097] The wastewater obtained in S5 is adsorbed and removed by ion exchange resin, and after the ion exchange resin is saturated with adsorption, 5wt% citric acid is used for elution.

[0098] Wherein, the preparation method of the composite precipitant is as follows:

[0099] 1) Deionized water, a 15 wt% sodium citrate solution, anhydrous ethanol, a 26 wt% ammonia solution and a 53 wt% polyvinylpyrrolidone hexanol solution were mixed uniformly in a volume ratio of 4:1:13:1:150 to obtain a microemulsion, and then the microemulsion was mixed uniformly with tetraethoxysilane in a volume ratio of 4.5:1, and the mixture was reacted at a constant temperature of 42°C for 7 hours. After the reaction was completed, the product was repeatedly washed with anhydrous ethanol and deionized water and then dried to obtain silica nanowires;

[0100] 2) 40 mL of polyethylene glycol was stirred and dissolved in 70 mL of deionized water, and then 1.3 g of sodium molybdate and 2.5 g of thiourea were added in sequence. After being fully stirred and dissolved, 0.16 g of polyvinyl pyrrolidone and 7 g of silica nanowires were added. After being fully stirred and dispersed evenly, the mixture was placed in a high-pressure reactor and stirred at 180 r / min for 12 h at 225 ° C. After the reaction was completed, the mixture was cooled to room temperature, washed repeatedly with anhydrous ethanol and deionized water, and then dried to obtain a composite nanomaterial. 7 g of the porous material was dispersed in 1000 mL of deionized water, and then 5 g of the composite nanomaterial was added. The mixture was mechanically stirred at 1300 r / min for 2 h, and then subjected to 400 W ultrasonic treatment for 40 min to obtain a composite porous material.

[0101] 3) In a constant temperature water bath at 55°C, add 13 g of β-cyclodextrin to 80 mL of a mixture of ethanol and deionized water in a volume ratio of 1:2.3, stir thoroughly to dissolve, then slowly add 0.5 g of lime, 0.3 g of calcium chloride and 23 g of the composite porous material, stir magnetically for 4 h, then cool naturally to room temperature, and refrigerate at 4°C overnight, pour off the supernatant, wash repeatedly with ethanol and deionized water, and freeze-dry for 4 h to obtain a composite precipitant.

[0102] The composite flocculant is composed of aluminum salt coagulant, polyacrylamide flocculant and flocculant enhancer in a mass ratio of 1:1.5:0.2;

[0103] The preparation method of the flocculation enhancer is as follows:

[0104] 1) 1.3 mol of potassium antimony tartrate was dissolved in 125 mL of deionized water, and after magnetic stirring for 15 min, 0.5 g of polyvinyl pyrrolidone was added, and stirring was continued for 15 min. Then, 2.1 mol of thioacetamide was added to the resulting mixed solution, and the mixture was fully stirred to obtain a reaction solution;

[0105] 2) 5 g of the porous material was ultrasonically cleaned with acetone, distilled water and ethanol for 15 min respectively, dried and added to 130 mL of the reaction solution. After ultrasonic treatment for 15 min, it was transferred to a reactor, sealed and placed in an oven, and heated at 182° C. for 26 h. After the reaction was completed, it was cooled to room temperature. The product was centrifuged, repeatedly washed with deionized water, and dried.

[0106] Example 3

[0107] A process for removing fluorine, silicon and hardness from photovoltaic wastewater, characterized in that it specifically comprises the following steps:

[0108] S1 Chemical Precipitation

[0109] Add composite precipitant and calcium hydroxide to photovoltaic wastewater and stir thoroughly until the pH value of the wastewater is 10;

[0110] S2 flocculation precipitation

[0111] Add a composite flocculant to the wastewater obtained in S1, stir thoroughly until flocculation precipitation is formed, and collect the supernatant;

[0112] S3 air flotation filtration

[0113] The supernatant obtained from S2 is pressurized and dissolved with air and then enters the flotation chamber, where the colloids and suspended matter formed in the water are separated, the scum is removed from the surface of the water body, and the treated wastewater is collected;

[0114] S4 Wastewater Hardness Removal

[0115] According to the Ca content in wastewater 2+ and Mg 2+ Weigh sodium hydroxide and sodium carbonate in an amount three times the total mass of the content, and then prepare them into reagents with a concentration of 18wt% and add them to the system reactor at the same time. The residence time of the wastewater in the hardness removal reactor is 80min.

[0116] S5 ion adsorption pretreatment

[0117] After the wastewater passes through the dosing and hardness removal reactor, it enters the Gore membrane filter. The pH of the effluent from the Gore membrane filter is adjusted, using hydrochloric acid as the reagent, and the pH value is adjusted to 6.5;

[0118] S6 ion adsorption

[0119] The wastewater obtained in S5 is adsorbed and removed by ion exchange resin, and after the ion exchange resin is saturated with adsorption, 7wt% citric acid is used for elution.

[0120] Wherein, the preparation method of the composite precipitant is as follows:

[0121] 1) Deionized water, a 16 wt% sodium citrate solution, anhydrous ethanol, a 27 wt% ammonia solution and a 56 wt% polyvinylpyrrolidone hexanol solution were mixed uniformly in a volume ratio of 5:1:15:1:180 to obtain a microemulsion, and then the microemulsion was mixed uniformly with tetraethoxysilane in a volume ratio of 5:1, and the mixture was reacted at a constant temperature of 45°C for 9 hours. After the reaction was completed, the product was repeatedly washed with anhydrous ethanol and deionized water and then dried to obtain silica nanowires;

[0122] 2) 50 mL of polyethylene glycol was stirred and dissolved in 100 mL of deionized water, and then 1.5 g of sodium molybdate and 2.7 g of thiourea were added in sequence. After being fully stirred and dissolved, 0.18 g of polyvinyl pyrrolidone and 10 g of silica nanowires were added. After being fully stirred and dispersed, the mixture was placed in a high-pressure reactor and stirred at 200 r / min for 15 h at 230 ° C. After the reaction was completed, the mixture was cooled to room temperature, washed repeatedly with anhydrous ethanol and deionized water, and then dried to obtain a composite nanomaterial. 10 g of the porous material was dispersed in 1200 mL of deionized water, and then 6 g of the composite nanomaterial was added. The mixture was mechanically stirred at 1500 r / min for 3 h, and then subjected to 500 W ultrasonic treatment for 50 min to obtain a composite porous material.

[0123] 3) In a constant temperature water bath at 60°C, add 15 g of β-cyclodextrin to 100 mL of a mixture of ethanol and deionized water in a volume ratio of 1:2.5, stir thoroughly to dissolve, then slowly add 0.7 g of lime, 0.5 g of calcium chloride and 25 g of the composite porous material, stir magnetically for 5 h, then cool naturally to room temperature, and refrigerate at 5°C overnight, pour off the supernatant, wash repeatedly with ethanol and deionized water, and freeze-dry for 5 h to obtain a composite precipitant.

[0124] Among them, the composite flocculant is composed of aluminum salt coagulant, polyacrylamide flocculant and flocculant enhancer in a mass ratio of 1:2:0.3;

[0125] The preparation method of the flocculation enhancer is as follows:

[0126] 1) 1.5 mol potassium antimony tartrate was dissolved in 150 mL deionized water, and after magnetic stirring for 20 min, 0.7 g polyvinyl pyrrolidone was added, and stirring was continued for 20 min. Then, 2.6 mol thioacetamide was added to the resulting mixed solution, and the mixture was fully stirred to obtain a reaction solution;

[0127] 2) 7 g of the porous material was ultrasonically cleaned with acetone, distilled water and ethanol for 20 min respectively, dried and added to 150 mL of reaction solution. After ultrasonic treatment for 20 min, it was transferred to a reactor, sealed and placed in an oven, and heated at 185° C. for 30 h. After the reaction was completed, it was cooled to room temperature. The product was centrifuged, repeatedly washed with deionized water, and dried.

[0128] Comparative Example 1: This comparative example is basically the same as Example 1, except that it does not contain a composite precipitant.

[0129] Comparative Example 2: This comparative example is basically the same as Example 1, except that a mixture of lime and calcium chloride in a mass ratio of 1:1 is used to replace an equal amount of the composite precipitant.

[0130] Comparative Example 3: This comparative example is basically the same as Example 1, except that the composite flocculant does not contain a flocculant enhancer.

[0131] Test experiment:

[0132] Wastewater from a photovoltaic plant, with a treatment capacity of 100m 3 / h, the water body contains 1800 mg / L of silicon, 120 mg / L of fluorine, 400 mg / L of calcium, and 125 mg / L of magnesium; the wastewater is treated by the methods provided in Examples 1-3 and Comparative Examples 1-3, respectively, and then the treated wastewater is tested, the contents of silicon, fluorine, calcium, and magnesium ions in the effluent are recorded, and the removal rate is calculated. The results are shown in Table 1.

[0133] Table 1

[0134]

[0135]

[0136] It can be seen from Table 1 that the wastewater treatment process provided by the present invention has a high removal rate of silicon and fluoride ions and low effluent hardness, and achieves the removal of fluorine, silicon and hardness of the wastewater, so that photovoltaic wastewater meets the first-class pollutant emission standards and the first-level standard. The effluent water quality is stable and suitable for industrial applications. It can be reused as industrial tap water to achieve the recycling of water resources.

[0137] The preferred embodiments of the present invention disclosed above are only used to help illustrate the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to the specific implementation methods described. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.

Claims

1. A process for removing fluorine, silicon and hardness from photovoltaic wastewater, characterized in that: The specific steps include: S1 Chemical Precipitation Add composite precipitant and calcium hydroxide to photovoltaic wastewater and stir thoroughly until the pH value of the wastewater is 9-10; S2 flocculation precipitation Add a composite flocculant to the wastewater obtained in S1, stir thoroughly until flocculation precipitation is formed, and collect the supernatant; S3 air flotation filtration The supernatant obtained from S2 is pressurized and dissolved with air and then enters the flotation chamber, where the colloids and suspended matter formed in the water are separated, the scum is removed from the surface of the water body, and the treated wastewater is collected; S4 Wastewater Hardness Removal According to the Ca content in wastewater 2+ and Mg 2+ Weigh sodium hydroxide and sodium carbonate in an amount 2-3 times the total mass of the content, and then prepare them into reagents with a concentration of 10-18wt%, and add them to the hardness removal reactor at the same time. The residence time of the wastewater in the hardness removal reactor is 60-80min; S5 ion adsorption pretreatment After the wastewater passes through the dosing and hardness removal reactor, it enters the Gore membrane filter. The pH of the effluent from the Gore membrane filter is adjusted, using hydrochloric acid as the reagent, and the pH value is adjusted to 6.0-6.5; S6 ion adsorption The wastewater obtained in S5 is adsorbed and removed by ion exchange resin, and after the ion exchange resin is saturated with adsorption, 3-7wt% citric acid is used for elution; The composite precipitant is prepared by the following method: 1) Deionized water, sodium citrate solution, anhydrous ethanol, ammonia water and polyvinyl pyrrolidone hexanol solution are mixed uniformly to obtain a microemulsion, and then the microemulsion is mixed uniformly with tetraethoxysilane in a volume ratio of (4-5):1, and the mixture is reacted at a constant temperature of 40-45°C for 4-9 hours. After the reaction is completed, the product is repeatedly washed with anhydrous ethanol and deionized water and then dried to obtain silica nanowires; 2) stirring and dissolving polyethylene glycol in deionized water, then adding sodium molybdate and thiourea in sequence, stirring and dissolving fully, then adding polyvinyl pyrrolidone and silicon dioxide nanowires, stirring and dispersing uniformly, placing in a high-pressure reactor, stirring at 150-200 r / min, and reacting at a constant temperature of 220-230° C. for 8-15 hours, cooling to room temperature after the reaction is completed, repeatedly washing with anhydrous ethanol and deionized water, and drying to obtain a composite nanomaterial, dispersing the porous material in deionized water, and then adding the composite nanomaterial, mechanically stirring at 1000-1500 r / min for 1-3 hours, and then ultrasonically treating at 300-500W for 30-50 minutes to obtain a composite porous material; 3) In a constant temperature water bath at 50-60°C, add β-cyclodextrin to a mixture of ethanol and deionized water in a volume ratio of 1: (2.0-2.5), stir thoroughly to dissolve, then slowly add lime, calcium chloride and the composite porous material, stir magnetically for 3-5 hours, then cool naturally to room temperature, and refrigerate at 3-5°C overnight, pour off the supernatant, wash repeatedly with ethanol and deionized water, and freeze-dry for 3-5 hours to obtain a composite precipitant.

2. A process for removing fluorine, silicon and hardness from photovoltaic wastewater according to claim 1, characterized in that: The composite precipitant is added in an amount of 8-15% of the total amount of wastewater; The calcium hydroxide is added in an amount of 10-18% of the total amount of wastewater; The composite flocculant is added in an amount of 3-5 g / L; The pressure of the pressurized dissolved gas is 4-6N.

3. The process for removing fluorine, silicon and hardness from photovoltaic wastewater according to claim 1, characterized in that: The main operation process of the Gore membrane filter is filtration, exhaust, pressure relief, backwashing, sedimentation, and slag discharge. The main operation parameters are: filtration pressure 0.01-0.10MPa, filtration time 1500-3500s, exhaust time 10-18s, backwashing time 10-20s, sedimentation time 20-50s, and slag discharge time 10-15s; The flow rate of the resin adsorption column of the ion exchange resin is controlled at 10-13 BV.

4. The process for removing fluorine, silicon and hardness from photovoltaic wastewater according to claim 1, characterized in that: The volume ratio of the deionized water, sodium citrate solution, anhydrous ethanol, ammonia water, and polyvinyl pyrrolidone hexanol solution is (3-5):1:(10-15):1:(100-180); The sodium citrate solution has a concentration of 12-16wt%; The ammonia water has a concentration of 25-27wt%; The polyvinyl pyrrolidone hexanol solution has a concentration of 50-56wt%.

5. The process for removing fluorine, silicon and hardness from photovoltaic wastewater according to claim 1, characterized in that: The ratio of polyethylene glycol, deionized water, sodium molybdate, thiourea, polyvinyl pyrrolidone and silica nanowires is (30-50) mL: (50-100) mL: (1.0-1.5) g: (1.8-2.7) g: (0.15-0.18) g: (5-10) g; The ratio of the porous material, deionized water, and composite nanomaterial is (5-10) g: (800-1200) mL: (3-6) g; The ratio of the β-cyclodextrin, the mixed solution, lime, calcium chloride and the composite porous material is (10-15) g: (60-100) mL: (0.3-0.7) g: (0.2-0.5) g: (20-25) g.

6. The process for removing fluorine, silicon and hardness from photovoltaic wastewater according to claim 1, characterized in that: The composite flocculant is composed of an aluminum salt coagulant, a polyacrylamide flocculant and a flocculant enhancer in a mass ratio of 1: (1-2): (0.1-0.3); The flocculant enhancer is prepared by the following method: 1) Dissolve potassium antimony tartrate in deionized water, stir magnetically for 10-20 minutes, add polyvinyl pyrrolidone, continue stirring for 10-20 minutes, then add thioacetamide to the resulting mixed solution, stir thoroughly to obtain a reaction solution; 2) The porous material is ultrasonically cleaned with acetone, distilled water and ethanol for 10-20 minutes respectively, and then added to the reaction solution after drying. After ultrasonic treatment for 10-20 minutes, it is transferred to a reactor, sealed and placed in an oven, and heated at a constant temperature of 180-185°C for 25-30 hours. After the reaction is completed, it is cooled to room temperature, the product is centrifuged, repeatedly washed with deionized water, and dried.

7. A process for removing fluorine, silicon and hardness from photovoltaic wastewater according to claim 6, characterized in that: The ratio of potassium antimony tartrate, deionized water, polyvinyl pyrrolidone and thioacetamide is (0.8-1.5) mol: (80-150) mL: (0.4-0.7) g: (1.5-2.6) mol; The ratio of the porous material to the reaction solution is (3-7) g: (100-150) mL; The ultrasonic treatment has a power of 200-300W.

8. A process for removing fluorine, silicon and hardness from photovoltaic wastewater according to claim 3 or 7, characterized in that: The porous material is prepared by the following method: 1) Disperse polyvinyl pyrrolidone in acetonitrile, add p-phenylenediamine and trimesic acid, treat with ultrasound for 10-15 minutes, then add scandium trifluoromethanesulfonate, stir for 5-10 minutes, stand at room temperature for 6-10 hours, and then centrifuge. 2) The obtained product is repeatedly washed with anhydrous ethanol and 1,4-dioxane, respectively, and then dispersed in a mixed solution consisting of 1,4-dioxane, mesitylene, deionized water and glacial acetic acid, and crystallized at 50-55° C. for 12-15 hours; after the reaction is completed, it is cooled to room temperature, centrifuged to separate the mother liquor, repeatedly washed with anhydrous ethanol, dispersed in n-octane and stirred for 12-15 hours to remove impurities, and dried after centrifugal separation to obtain a porous material.

9. A process for removing fluorine, silicon and hardness from photovoltaic wastewater according to claim 8, characterized in that: In the method for preparing the porous material: The ratio of polyvinyl pyrrolidone, acetonitrile, p-phenylenediamine, benzene trimethylenedialdehyde, scandium trifluoromethanesulfonate, 1,4-dioxane, mesitylene, deionized water, and glacial acetic acid is (200-300) mg: (15-25) mL: (0.23-0.28) mmol: (0.15-0.20) mmol: (1-3) mg: (10-13) mL: (2.5-3.6) mL: (2.5-3.6) mL: (3.5-5.0) mL; The ultrasonic treatment has a power of 200-300W; The stirring speed is 500-800r / min.

Citation Information

Patent Citations

  • Efficient silicon and fluorine removal system and method for photovoltaic wastewater

    CN112158983A

  • Defluorinating method of photovoltaic wastewater

    CN102001766A

  • Advanced wastewater hardness removal method

    CN102372375A

  • High-strength and high-fluidity composite admixture for concrete and preparation method of high-strength and high-fluidity composite admixture

    CN115093155A

  • Degradable oiling agent for nylon high-temperature-resistant anti-yellowing spinning and preparation method thereof

    CN115897216A